Evaluating artistic research - L'évaluation de la recherche artistique - Campos, Rémy; Poidevin, Aurélien (Paris Editions l'oeuil d'or, 2019)
When the main conservatoires of music, art schools and universities of the arts joined the European higher education area twenty years ago, the question of how to evaluate artistic research immediately arose. On the initiative of the Haute école de musique de Genève, this book offers a reflection on the ways in which research results and procedures are assessed in the worlds of art. It brings together contributions from various players in the academic world concerned with the evaluation of artistic research: institutional managers, teacher-researchers, project promoters and practitioners. (Translated with DeepL.com)
Keywords: Artistic research